Unprocessed real-time imaging of vitreoretinal surgical maneuvers using a microscope-integrated spectral-domain optical coherence tomography system - Hahn, Paul; Migacz, Justin; O’Connell, Rachelle; Izatt, Joseph A.; Toth, Cynthia A. (Graefe's archive for clinical and experimental ophthalmology, 2013)
Background We have recently developed a microscope-integrated spectral-domain optical coherence tomography (MIOCT) device towards intrasurgical cross-sectional imaging of surgical maneuvers. In this report, we explore the capability of MIOCT to acquire real-time video imaging of vitreoretinal surgical maneuvers without post-processing modifications. Methods Standard 3-port vitrectomy was performed in human during scheduled surgery as well as in cadaveric porcine eyes. MIOCT imaging of human subjects was performed in healthy normal volunteers and intraoperatively at a normal pause immediately following surgical manipulations, under an Institutional Review Board-approved protocol, with informed consent from all subjects. Video MIOCT imaging of live surgical manipulations was performed in cadaveric porcine eyes by carefully aligning B-scans with instrument orientation and movement. Inverted imaging was performed by lengthening of the reference arm to a position beyond the choroid. Results Unprocessed MIOCT imaging was successfully obtained in healthy human volunteers and in human patients undergoing surgery, with visualization of post-surgical changes in unprocessed single B-scans. Real-time, unprocessed MIOCT video imaging was successfully obtained in cadaveric porcine eyes during brushing of the retina with the Tano scraper, peeling of superficial retinal tissue with intraocular forceps, and separation of the posterior hyaloid face. Real-time inverted imaging enabled imaging without complex conjugate artifacts. Conclusions MIOCT is capable of unprocessed imaging of the macula in human patients undergoing surgery and of unprocessed, real-time, video imaging of surgical maneuvers in model eyes. These capabilities represent an important step towards development of MIOCT for efficient, real-time imaging of manipulations during human surgery.